Breaking into the Hebrew verb system: A learning problem. Issue 5 (October 2016) - Ashkenazi, Orit; Ravid, Dorit; Gillis, Steven
Verb learning is an important part of linguistic acquisition. The present study examines the early phases of verb acquisition in Hebrew, a language with complex derivational and inflectional verb morphology, analyzing verbs in dense recordings of CDS and CS of two Hebrew-speaking parent–child dyads aged 1;8–2;2. The goal was to pinpoint those cues that help toddlers identify the root-and-pattern make-up of Hebrew verbs despite the prevalence of structural opacity and irregularity in the verbs they hear, due to a high token frequency of defective (irregular)-root verbs. The study provides a detailed account of the distribution of root types and temporal categories in Hebrew CDS and CS showing how verb specific morphological features in the form of inflectional affixes in the Modal Cluster of Infinitive Imperative and Future Tense in CDS act as distributional cues facilitating verb acquisition in CS.